TANTANGAN GLOBALISASI PENDIDIKAN ISLAM (Study Komparasi Budaya Pop di Indonesia dan Malaysia) - Husniyah, Nur Iftitahul (Akademika, 2017)
Popular culture broadcast from electronic media in this paper is aimed at introdution children to the importance of good moral messages in addition to being a medium of Islamic religious education transfer in the matters of worship or moral and social values. Animated Upin Ipin film produced in Malaysia, the business management, creative ideas, and quality of the image could deliver the Upin & Ipin film in getting some awards. In 2008, Upin & Ipin was awarded International Achievement Appreciation Award, Best of Media Entertainment Category-Merit Award (MSC Malaysia APICTA 2008), and President's Award (Malaysia-Canada Business Council Business Excellence 2008). Meanwhile, in 2009, it was awarded Winner of MSC-Malaysia Management Game 2009, IT Frank 2009 (Global Emerging Innovative Enterpreneur), First 3D Animation Feature Film (Malaysia Book of Records), Viewer Choice Award (Kids Film Festival), Anugerah Khas JuriÂ  and Anugerah Box Office (Malaysia Film Festival), Best on Screen Chemistry Awards (Shout Awards), and Best Editing and Best Music (MSC Creative Digital Contents Conference). These awards have once again marked the high quality of Upin & Ipin series and Upin & Ipin technology innovation in Malaysia.